Prosodic disambiguation of the Mandarin discourse marker Fanzheng (“anyway”): A corpus-based study of functional asymmetry at utterance peripheries - Shan, Yi; Chu, Weiwei (Journal of pragmatics, 2025)
This study investigates the prosody-pragmatics interface of the Mandarin Chinese discourse marker (DM) fanzheng in spontaneous conversation, focusing on how prosodic features contribute to its functional differentiation at the left and right peripheries of utterances. Using data from the CABank Mandarin CallFriend Mainland Corpus, we conducted a comparative analysis of 322 tokens of fanzheng, examining their distribution, prosodic characteristics, and pragmatic functions. Our findings reveal a significant distributional asymmetry, with 82 % of tokens occurring at the left periphery and 12 % at the right periphery. This asymmetry correlates with distinct functional roles, supporting the concept of functional asymmetry in DMs. Prosodic analysis across multiple variables (duration, tempo, intensity, and pause duration) showed significant differences between left- and right-periphery tokens. Based on these differences, we constructed a prosody-periphery model that achieved 97 % accuracy in classifying fanzheng tokens, demonstrating the potential of prosodic features in disambiguating DM functions. The study contributes to the growing body of research on the prosody-pragmatics interface by providing empirical evidence for the role of prosody in disambiguating DM functions and offering a replicable methodology for investigating other DMs. Our findings align with previous research on DM prosody across languages while also highlighting language-specific factors that influence DM usage. This research has implications for language pedagogy, natural language processing, and future studies in discourse analysis. It underscores the need for further cross-linguistic research to explore potential universal patterns in the prosody-pragmatics interface of DMs and calls for investigating the intentional exploitation of prosodic ambiguity in communication strategies. •Investigating the prosody-pragmatics interface of 322 fanzheng tokens.•Correlating distributional asymmetry with functional asymmetry.•Prosodic variables performing differently at left- and right-peripheries.•Constructing a prosody-periphery model with a 97 % accuracy in classifying tokens.•Demonstrating the potential of prosody in disambiguating functions.